Brazilian contributions to Community Psychology - Denise Jodelet (Estudos de Psicologia, 2013)
This paper presents a research current that has spread over Brazil: the Community Psychology that is now recognized as an autonomous subject and that is supported by Anglo-Saxon and European countries where national and international associations are being multiplied. The analysis of some aspects of this subject allows for outlining some relevant remarks to subsidize our discussion: values, principles and models of action that are common or specific in this discipline; aspects of social dimension to the approaches of Community Psychology and its places of observation and application.